Effect of Adding Konjac Glucomannan on the Physicochemical Properties of Indica Rice Flour and the Quality of Its Product of Instant Dry Rice Noodles - Chunmiao Lu; Ying Yang; Xin Zhao; Zhiyu Liu; Xiaoyan Liao; Yingying Zhang; Dailin Wu; Jing Li; Jiangtao Li (Foods, 2024)
Instant dry rice noodles have a broad market prospect due to their advantages of long shelf life, convenient transportation, and convenient eating, but there are still quality problems such as long rehydration times and poor eating quality. In order to improve the quality of instant dry rice noodles, the effects of konjac glucomannan (KGM) on the gelatinization characteristics, pasting properties, and rheological properties of Indica rice flour and the structure, food quality, and starch digestibility of instant dry rice noodles made of Indica rice flour were studied. The results showed that the starch gelatinization conclusion temperature and endothermic enthalpy of Indica rice flour were reduced by adding ≤ 3% KGM, the peak viscosity, valley viscosity, final viscosity, and setback value of Indica rice flour in the pasting process decreased with the increase in the KGM addition amount, and the pseudoplasticity, viscosity, and elasticity of Indica rice flour paste were reduced by adding > 1% KGM. When the KGM addition amount was 2%, the endothermic enthalpy, final viscosity, and setback value of Indica rice flour were 2.74 J/g, 2379.5 cp, and 961.5 cp, respectively. The instant dry rice noodles made of Indica rice flour had a looser microstructure after adding KGM, and its short-range ordered structure and double helix content were reduced by adding 1~3% KGM. When the KGM addition amount was 2%, the rehydration time of instant dry rice noodles was 290 s, which was shortened by 14.7%, while the texture and sensory quality remained unchanged, and the SDS content was reduced by 16.4% while the RS content was increased by 28.8%. Therefore, the physicochemical properties of Indica rice flour and the quality of its instant dry rice noodles can be improved by adding an appropriate amount of KGM. This study can promote the application of KGM in improving the quality of rice products.